Information Revolution: How INFORMATION MANAGEMENT is CHANGING the Lives of Rural People - Sultan, Jacques; Mundy, Paul (Technical Centre for Agricultural and Rural Cooperation, 2001)
This book is about successes. It is about how certain individuals or organizations are changing the way communication works, how they are making a difference to the lives and livelihoods of rural people...